The ethical dimension of psychoanalysis : a dialogue - Meissner, W. W. (William W.), 1931-2010 (SUNY series in psychoanalysis and culture., 2003)
"Addressing the common ground between ethics and psychoanalysis, W.W. Meissner asks "Does psychoanalysis have anything to contribute to ethical understanding and reflection?" and conversely, "Does ethics have anything to offer analytic understanding of the complexities of human behavior and decision-making?" Both disciplines focus their interest and concern not only on the inner well-being of the individual, but also on questions of his or her adaptation to the outside world, including both intimate personal relations as well as broader societal and communal relations. This book explores and explicates areas of interaction and common interest between these two disciplines in the hope of opening the way to further exploration and dialogue in the understanding of the human phenomenon."--Jacket